Islamic Education Management Strategy in the Digital Era: Governance Transformation to Increase Effectiveness and Accessibility - Yuliati A. S; Susi Ernawati; Hardika Saputra; M. Agus Kurniawan (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
The digital era has brought significant transformations to the field of education, including Islamic education. Technology such as the internet, mobile devices, and e-learning platforms have shifted learning models from teacher-centered to student-centered approaches, making education more accessible and flexible. However, Islamic educational institutions like madrasas and pesantrens face unique challenges in integrating technology due to limitations in infrastructure, educator skills, and concerns about preserving Islamic values. This paper explores the opportunities and challenges posed by digitalization for Islamic education, focusing on infrastructure gaps, training needs for educators, and the cultural concerns surrounding the use of technology. The paper also highlights successful case studies from institutions like Madrasah Al-Irsyad and the International Islamic University Malaysia, showing how strategic management and government support can help overcome these challenges. It concludes by emphasizing the importance of integrating technology while maintaining the core values of Islamic education.